2020
DOI: 10.33448/rsd-v9i11.10247
|View full text |Cite
|
Sign up to set email alerts
|

Obtenção e caracterização de hidroxiapatita obtida por síntese hidrotermal e caracterização

Abstract: A hidroxiapatita (HA) é um material cerâmico presente em ossos e dentes humanos, com isso a HA sintética possui propriedades de osteointegração e biocompatibilidade, sendo amplamente utilizada em implantes e próteses. Uma das formas de sintetizar a HA é pelo método hidrotermal, um método eficiente que permite realizar o controle de temperatura e pressão, gerando produtos de alta cristalinidade. Este trabalho visou à obtenção da HA por via hidrotermal, que foi analisada sob diferentes formas de caracterização. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…They are also beneficial in the chemical modification of hydroxyapatite nanoparticles' surface and are achieved through functionalization, which introduces functional groups that enhance the effective attachment of therapeutic materials, targeting, and release [112]. CHA synthesis methods can be grouped into two: wet and dry synthesis methods [4,[113][114][115][116].…”
Section: Synthesis Methods and Characterizationmentioning
confidence: 99%
“…They are also beneficial in the chemical modification of hydroxyapatite nanoparticles' surface and are achieved through functionalization, which introduces functional groups that enhance the effective attachment of therapeutic materials, targeting, and release [112]. CHA synthesis methods can be grouped into two: wet and dry synthesis methods [4,[113][114][115][116].…”
Section: Synthesis Methods and Characterizationmentioning
confidence: 99%
“…The synthesis of stoichiometric hydroxyapatite (HAp) has been widely studied for decades (Araújo et al, 2020;Bonel et al, 1988;Brown et al, 1991;Greish, 2011;Kakiage et al, 2015), but only a few authors have reported results on the synthesis of calcium-rich HAp sintering or characteristics of HAp and CaO (Bengtsson et al, 2009;Kim et al, 2005;Omori et al, 2014;Raynaud et al, 2002).…”
Section: Introductionmentioning
confidence: 99%